The influence of key opinion leaders on consumers' purchasing intention regarding green fashion products - Tran, Khanh Vi; Uehara, Takuro (Frontiers in Communication, 2023)
Using Key Opinion Leaders (KOLs) is an emerging marketing strategy to promote green fashion products. However, research on the influence of KOLs on consumers' purchase intentions for green fashion products remains insufficient. Therefore, this study investigated how KOLs gained consumer trust and affected their green purchase intentions by applying the stimulus-organism-response (SOR) framework. Based on a literature review, this study considers KOL features, including reputation, perceived fit, and production involvement, and KOL content features, including content quality, aesthetic quality, and interactive content. To empirically verify these relationships, we conducted an online survey of Vietnamese consumers. We collected four hundred valid responses and employed structural equation modeling (SEM) to test the hypotheses based on the SOR framework. Of the six latent variables, KOL's perceived fit and interactive content were positively associated with consumer trust and strengthened their intention to make green purchases. Given the limited knowledge and low awareness of organizations of green products, this study recommends leveraging KOLs as a powerful marketing method to provide consumers with a more comprehensive understanding of the benefits associated with green fashion products. Furthermore, the limited applicability of the SOR framework (two of the six latent variables were significant) reveals the need for more studies on KOLs by further testing the SOR framework in different contexts or using alternative frameworks.